Phlebotomine fauna in a rural area of the Brazilian Pantanal - Braga-Miranda Lourdislene Costa; Miranda Marcos; Galati Eunice A Bianchi (Universidade de São Paulo, 2006)
The aim of the study was to identify among the phlebotomine fauna potential leishmaniasis vectors. The study was carried out in Corumbá county, State of Mato Grosso do Sul, Mid-West Brazil (18º59'S, 56º39'W). Sand fly captures were undertaken fortnightly with automatic light traps at 11 sites in forested environments and anthropic areas from April 2001 to July 2003. A total of only 41 specimens were captured. Thirty-one percent of the specimens were captured in forests and 68.3% in anthropic areas. The predominance of non-anthropophilic groups and the low density of N. whitmani, a known cutaneous leishmaniasis vector, does not seem to indicate any actual risk of the transmission of this disease in the study area.